Media Coverage Influence on ESG-Firm Value Nexus in 3 ASEAN Public Palm Oil Industry - Khalilul Rahman; Yurniwati (Jurnal Dinamika Akuntansi, 2026)
Purposes: This study investigates the impact of ESG performance on firm value in the palm oil sector, with a particular focus on the moderating role of media coverage.Methods: This study employs OLS regression analysis using data from 27 palm oil companies listedon SPOTT in Indonesia, Malaysia, and Singapore over the period 2020–2023. The analysis combinesESG and media coverage data from SPOTT with financial metrics obtained from Thomson Reuters.Findings: The findings reveal a significant negative relationship between ESG performance (bothcomposite scores and individual components) and firm value, reflecting market skepticism towardsustainability investments in this resource-intensive industry. Importantly, media coverage is identified as a positive moderator that mitigates the valuation discounts associated with ESG initiatives.Novelty: This study extends prior research by applying the role of media coverage as a moderatingvariable in the ESG–firm value nexus within the palm oil industry context. The results providepractical implications for companies to enhance ESG transparency and strategically manage medianarratives to shape stakeholder perceptions, while regulators are encouraged to consider media dynamics in ESG reporting frameworks to improve market responses.